Investigating how mediation tools enhance rural farmers' learning towards rainwater harvesting and food security: a case study of a Green Village programme - Shawarira, Patience (Rhodes University, Faculty of Education, Department of Education, 2019)
Training programmes are often detached from people's context and experiences. It is critical that training programmes are carefully situated and relevant to the target group. This can be achieved through the use of relevant mediation tools. This study investigates how the use of mediation tools within a training programme on rainwater harvesting and conservation conducted by the Water Research Commission (WRC) funded the Green Village project impacted on Community Works Project (CWP) farmers' practices. The study looks at how rural farmer learning occurs through the use of mediation tools in the context of the CWP farmers operating in Sinxaku village, in the Eastern Cape, South Africa. The learning process in this study was tracked through observing a three-day training workshop. I observed the Green Village facilitator's choice and use of mediation tools to facilitate learning during the training. I looked at ways in which the Green Village facilitator engaged with the participants during the training and how they used different mediation tools to aid the learning process. I was interested in how the CWP farmers engaged with the mediation tools and how learning occurred from the training. I also looked out for changes in the CWP farmers' farming practices following the completion of the training. The study constituted as an interpretative case study using Cultural Historical Activity (CHAT) theoretical tools. The study also drew on previous research on mediation and learning processes in the water management sector. Using interviews, observations and document analyses, the study found that rural farmers learn better by practising what they are being taught. They also learn from visuals and illustrations as these explain technical concepts in a clear and easy to understand manner. Factors that impact on rural farmer learning, particularly in the context of the CWP farmers operating in Sinxaku village include ecological factors, availability of farm equipment and the structuring of the training programme. The study found that in facilitating a training programme with rural farmers, more time should be given to practical activities at the demonstration site and that these practical activities should be interspersed with knowledge sharing in a workshop setup. The study concluded that special attention should be given to the choice of mediation tools used in training programmes involving rural farmers. Attention should also be given to contextual factors that can potentially impact on learning and practice of rainwater harvesting and conservation practices that would have been taught in a training programme.
Keywords: Mediated learning experience; Environmental education -- South Africa -- Sinxaku; Agricultural education -- South Africa -- Sinxaku; South Africa. Water Research Commission. Green Village Lighthouse